Atrial fibrillation associated with high voltage electric shock in a young healthy female: a case report - Kant, Priyesh; Singh, P. S.; Zafar, Khwaja Saifullah; Rawat, Ramakant (International Journal of Research in Medical Sciences, 2017)
Atrial fibrillation is amongst the various arrhythmias resulting after electrical injury but its incidence has been reported to be extremely rare. Here we are reporting a case of 35 years old lady presenting to our Emergency department with atrial fibrillation with fast ventricular rate after accidentally being injured by high voltage electrical current. She was managed successfully with pharmacological cardioversion followed by a period of observation. The rhythm reverted back to normal sinus rhythm on 3rd day. This approach of management is amongst one of the few published cases where patient was managed conservatively.